Answer:
X=-2
Y=-6
Step-by-step explanation:
Since both equations are already expressed in the simplest form of y, then we equate them to be equal hence
x-4=4x+2
Bringing like terms together
-4-2=4x-x
Solving both sides
-6=3x
Making x the subject then
X=-6/3=-2
Subsrituting the value of x into any of the initial equations
Y=x-4 then y=-2-4=-6
Therefore, the solution is
X=-2
Y=-6
Answer:
A≈78.54
Step-by-step explanation:
A=πr2
I think this is right
Angle C, it sounds obvious but they correspond to the angle in the same order as them, as both E and C are in the middle it has to be C.